Compreensão de textos escritos entre alunos iniciantes de Letras da UNEAL - Bezerra, Jane Cleide dos Santos (2012)
The theme of this dissertation is related to written text comprehension among beginner students of the course of Languages at the State University of Alagoas (UNEAL). The relevance of the theme concerns to the fact that the students are in a native and foreign language teacher formation program and, because of this, they must have a reasonable proficiency in reading comprehension, not only for their good academic performance, but also to face teaching this ability in their future professional activities. However, in our pedagogical practice at the university, we have ascertained that many of these undergraduate students still present serious difficulties in reading comprehension, maybe caused by deficiency in their basic education. In this sense, the objective of this research was to verify reading comprehension among university students from the Languages course as informants, who studied in the evening during the year of 2008, in the municipality of Arapiraca, in interior of Alagoas State, in the Northeast of Brazil. This research can be viewed as interpretative, qualitative and ethnographic, more specifically, a case study. To collect data, the author used a questionnaire to obtain students’ profile and, in order to evaluate reading comprehension, the author applied three cloze tests; three multiple choice comprehension tests, and besides, she utilized post-reading protocols. To provide a scientific foundation for the work, the author has seen the object of study – reading – in three ways: 1) the social function of reading; 2) the internal reading processing, including conceptions, reading models and cognitive and metacognitive strategies and 3) the importance of research in reading and its instruments. The results showed that the students had more difficulties in comprehending texts which had argumentative structure, revealing some lacks from basic education. This problem interferes in the apprehension of academic texts and these lacks must be provided by the graduation courses at the university so as the informant students do not feed back the low levels of comprehension that exists among high school students nowadays.